Exploring the complex mechanisms of post-intracerebral hemorrhage depression: towards personalized treatment approaches - Li, Pengpeng; Gao, Yangyang (Frontiers in Psychiatry, 2025)
Post - stroke depression (PSD) is a common mental disorder after stroke that significantly impacts patients’ quality of life. While research on depression after ischemic stroke has made progress, the mechanisms of depression after cerebral hemorrhage remain unclear. The incidence of depression after cerebral hemorrhage is high, ranging from 18% to 60%, which greatly affects patients’ rehabilitation and quality of life. This article reviews the pathogenesis, clinical manifestations, and treatment approaches for depression following intracerebral hemorrhage (ICH), emphasizing its distinct characteristics and therapeutic challenges, while also outlining potential directions for future research. The development of depression after ICH is multifactorial and complex. Firstly, disruptions in neurotransmitter systems may be a critical underlying mechanism. Secondly, neuroinflammatory processes likely contribute to its onset. Additionally, the interplay between neural network reorganization and psychosocial factors must also be considered. Current treatments for depression after a brain bleed include medication, non-drug therapies, and teamwork among healthcare professionals. Medications can help balance brain chemicals to reduce symptoms. Non-drug therapies, like counseling and support groups, offer emotional help and ways to manage stress. Working together, doctors, therapists, and other experts create personalized plans to improve recovery. Future research should focus on combining precision medicine and new technologies to improve personalized treatment and practical use for depression after ICH. Precision medicine can customize care based on a patient’s unique traits, such as genetic data and biological markers. Advances in brain imaging and genetic testing can help us better understand the causes of this condition and provide more effective and tailored treatments.